2013
DOI: 10.1111/mbe.12028
|View full text |Cite
|
Sign up to set email alerts
|

Once Upon a Time: Parent–Child Dialogue and Storybook Reading in the Electronic Era

Abstract: Early experiences with books predict later reading success, and an interactive shared reading style called “dialogic reading” is especially beneficial to emergent literacy. Electronic console (EC) books, CD‐rom books, and e‐book apps are designed to teach preschoolers preliteracy skills, but research has yet to systematically explore the impact of these types of books on established predictors of positive literacy outcomes. This research fills that gap with two studies investigating dialogic language and child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
4
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(168 citation statements)
references
References 57 publications
10
140
4
14
Order By: Relevance
“…Some studies suggested that, just like traditional books, e-books can serve as educational tools to support language growth, and they are especially beneficial for low-SES children (Korat & Shamir 2008, Korat et al 2014). In contrast, other studies showed that the presence of electronic features might distract children's attention and hinder their learning during book-reading interactions (Parish-Morris et al 2013). It appears that the key factor is not whether learning materials are digital or print based, but whether they successfully elicit high-quality language interactions between children and caregivers to support children's engagement with the learning materials (Gong & Levy 2009, Segal-Drori et al 2010, Smeets & Bus 2015.…”
Section: Interventions Targeting Learning Resourcesmentioning
confidence: 91%
“…Some studies suggested that, just like traditional books, e-books can serve as educational tools to support language growth, and they are especially beneficial for low-SES children (Korat & Shamir 2008, Korat et al 2014). In contrast, other studies showed that the presence of electronic features might distract children's attention and hinder their learning during book-reading interactions (Parish-Morris et al 2013). It appears that the key factor is not whether learning materials are digital or print based, but whether they successfully elicit high-quality language interactions between children and caregivers to support children's engagement with the learning materials (Gong & Levy 2009, Segal-Drori et al 2010, Smeets & Bus 2015.…”
Section: Interventions Targeting Learning Resourcesmentioning
confidence: 91%
“…This study also indicated that when young children completed a puzzle on the touch screen compared to the 3-D puzzle, they tended to be less efficient and spent more time manoeuvring the 2-D pieces off-task, suggesting a certain level of distraction due to the technology (Moser et al, 2015). Similarly, a study of older children and parents using e-readers found that they became distracted by the technological interactivity of the medium, which then impacted on their story comprehension (Parish-Morris, Mahajan, Hirsh-Pasek, Golinkoff, & Collins, 2013). Finally, CYBER BABIES: THE IMPACT OF EMERGING TECHNOLOGY 512 exposure to and engagement with age-inappropriate apps by young children may waste valuable cognitive effort on content that is incomprehensible to them (Lillard et al, 2015).…”
Section: Learning From Screen Mediamentioning
confidence: 92%
“…Instead, recent studies highlight the importance of joint parent-child reading, show- ing that learning gains are achieved by combining the use of digital media with adult interaction (Segal-Drori et al 2010). Interactive stories tend to distract readers with multimedia features without increasing the dialog between parents and children during reading, which results in lower learning rates (Parish-Morris et al 2013).…”
Section: Introductionmentioning
confidence: 99%